Sunlight driven photocatalytic degradation of organic pollutants using a MnV2O6/BiVO4 heterojunction: mechanistic perception and degradation pathways. Issue 22 (30th September 2021) - Bano, Karina; Mittal, Susheel K.; Singh, Prit Pal; Kaushal, Sandeep
Abstract : In the field of photocatalysis, fabrication of a heterojunction structure with effective charge separation at the interface and charge shift to enhance the photocatalytic activity has acquired extensive consideration. Abstract : In the field of photocatalysis, fabrication of a heterojunction structure with effective charge separation at the interface and charge shift to enhance the photocatalytic activity has acquired extensive consideration. In the present investigation, MnV2 O6 /BiVO4 heterojunction samples with excellent photocatalytic performance under sunlight irradiation were conveniently synthesized by a hydrothermal technique, and characterized by UV-Vis, FTIR, XRD, FESEM, HRTEM, PL, BET and XPS techniques. The prepared samples were investigated as photocatalysts for degrading MB and RhB dyes under sunlight. Among various samples of MnV2 O6 /BiVO4, the S-V hetero-junction sample exhibited maximum photocatalytic activity with 98% and 96% degradation of MB and RhB dyes, respectively, in 6 and 35 min. The high photocatalytic activity of MnV2 O6 /BiVO4 may be due to the successful generation and shift of charges in the presence of visible light. The average reduction of chemical oxygen demand (COD) was found to be 75% after irradiation with direct sunlight. In the degradation process of dyes, superoxide anion radicals were the main responsive species, as revealed by trapping experiments. The degradation efficiency of MnV2 O6 /BiVO4 heterojunction did not diminish even after four cycles. In addition, the catalytic performance of the fabricated heterojunction was also explored for reducing 4-nitrophenols (4-NP) by using NaBH4 . Absolute conversion of 4-NP to 4-aminophenol (4-AP) occurred without the production of intermediate byproducts.